The influence of working conditions and employees’ income on the maintenance of audit human resources in domestic independent auditing firms - Sang, Phung Khac; Lan, Nguyen Ngoc; Phuong, Mai Quynh; Thanh, Nguyen Tien; Hai, Le Thi Thanh (Edelweiss Applied Science and Technology, 2025)
For the auditing industry, which is a high-pressure and seasonally characterized industry, regulations on overtime, night work, occupational health care, and work arrangements play a key role in reducing stress, occupational burnout, and enhancing human resource retention. The purpose of this paper is to analyze, evaluate, and measure the factors of working conditions and employee income affecting the retention of audit human resources in domestic independent audit firms in Vietnam. We use both qualitative and quantitative research methods. Data are collected from auditors working in domestic independent audit firms through survey forms. The results show that the retention of audit human resources in domestic independent audit firms is influenced by two factors: working conditions and employee income. Of which, working conditions have the greatest influence. Based on the research results, we propose some recommendations to promote the retention of audit human resources in domestic independent audit firms in Vietnam.